Total Knee Arthroplasty: Fitness, Heart Disease Risk, and Quality of Life - Casazza, Gretchen A.; Lum, Zachary C.; Giordani, Mauro; Meehan, John P. (The Journal of Knee Surgery, 2019)
Total knee arthroplasty (TKA) may decrease coronary heart disease (CHD) risk in patients with advanced osteoarthritis by reducing pain and allowing for a more active lifestyle. We examined cardiovascular fitness, CHD risk factors, and quality of life in patients for 1 year after TKA compared with matched controls who did not undergo surgery. A total of 14 patients, 7 surgery patients and 7 matched controls, were tested for measurements of body composition, knee range of motion, resting blood pressure, strength testing, a maximal exercise test, quality-of-life questionnaires (Medical Outcomes Study Short Form-36 and Knee Osteoarthritis Outcome Score [KOOS]), and activity monitoring, fasting blood glucose, and lipids at 0, 3, 6, and 12 months after surgery or baseline testing. Comparison between the two groups was analyzed. Twelve months after surgery, patients with TKA had significantly (p < 0.05) lower pain scores, increased fat free mass, lower resting mean arterial pressure, and improved scores on the KOOS for pain, symptoms, activities of daily living, and quality of life. Initially, total cholesterol, high-density lipoprotein cholesterol, triglycerides, and body fat percentage were reduced in the TKA group but returned to baseline at 12 months. The results of this study indicate that there are immediate and long-term improvements in pain and quality of life in patients with TKA, but physical function, exercise capacity, leg strength, and some lipid profiles may take longer than 12 months to improve. This is a level II, prospective, Therapeutic study, comparative study.
Keywords: TKA; total knee arthroplasty; lipid profile; exercise; fitness function